miR-668 inhibitor attenuates mitochondrial membrane potential and protects against neuronal apoptosis in cerebral ischemic stroke - He, Junna; Zhang, Xiangjian (Folia Neuropathologica, 2020)
Cerebral stroke is a major cause of brain injury due to the production of hypoxic conditions, and new therapeutic interventions are required for its management. Here, we evaluated the protective effect of miR-668 inhibitor against ischemia/reperfusion (I/R)-induced stroke. Cerebral stroke was induced by cerebral artery occlusion in rats, followed by treatment with miR-668 inhibitor for 10 minutes before reperfusion. The neuroprotective effect of miR-668 inhibitor was determined by estimating the neurological deficit score, cerebral infarct area and blood-brain barrier (BBB) permeability. In addition, the levels of inflammatory cytokines, and the expression of NLRP3, zonula occludens-1 (ZO-1), dynamin-related protein 1 (Drp1) and occludin proteins, were estimated by ELISA and Western blotting, respectively. TUNEL assay and immunohistochemical analyses were performed to examine the effects of miR-668 inhibitor against I/R-induced stroke rats. The miR-668 inhibitor treatment group showed reductions in the infarct area, BBB permeability and neurological score compared to the stroke group. The levels of cytokines and reactive oxygen species were reduced in the miR-668 inhibitor treatment group compared to the stroke group. These observations suggested that inhibition of miR-668 reduces neuronal apoptosis by ameliorating the expression of caspase 3, Bax and Bcl-2 protein in I/R stroke rats. The expression of NLRP3, ZO-1 and occludin proteins was attenuated in the brain tissue of the miR-668 inhibitor treatment group compared to the stroke group. Moreover, the phosphorylation of Drp1 protein was reduced in the miR-668 inhibitor group compared to the stroke group. In conclusion, the results of the present study indicated that inhibition of miR-668 prevented neuronal apoptosis in cerebral I/R-induced stroke by modulating mitochondrial function and regulating NLRP3 signalling.